Integrated analysis of lncRNA–mRNA co-expression networks in the α-particle induced carcinogenesis of human branchial epithelial cells. (1st February 2019) - Liu, Xiao-Dan; Xie, Da-Fei; Wang, Yi-Long; Guan, Hua; Huang, Rui-Xue; Zhou, Ping-Kun
Abstract: Purpose: To identify the mRNA and long noncoding RNA (lncRNA) expression profiles and explore the lncRNA–mRNA co-expression networks associated with the carcinogenesis induced by α-particles. Materials and methods: Immortalized human bronchial epithelial cell line, BEP2D, and its two malignant transformed cell lines, BERP35T-1 and BERP35T-4, were investigated. The lncRNA and mRNA expression profiles of BEP2D, BERP35T-1 and BERP35T-4 were generated. lncRNAs and mRNAs co-expression analysis was performed. Results: The microarray identified 668 lncRNAs in BERP35T-1 cells and 555 in BERP35T-4 cells that were differentially expressed compared to BEP2D cells. The GO terms and KEGG pathway annotation data indicated that mitotic cell cycle, DNA repair, apoptotic processes, and RNA splicing functional pathways were significantly associated with the α-particle induced cell carcinogenesis. Co-expression network analysis revealed 8902 interactions between 495 differentially expressed mRNAs and 430 corresponding lncRNAs in BERP35T-1 cells compared with BEP2D cells. The genes, situated at the important nodes of the co-expression network, include B3GNT5, RAD23, YWHAZ (14-3-3ζ), FBXW11, TGFBR2, LRP6, PSMD11, MYL12A, etc. Conclusions: This pilot study is the first to explore epigenetic mechanisms of α-particle induced carcinogenesis of human bronchial epithelial cells. It provides basic information for further investigation into the detail mechanisms underlying radiation-induced lung cancer.